Roles of histone acetyltransferases and deacetylases in gene regulation. - Kuo, M.H.; Allis, C.D. (BioEssays, 1998)
Acetylation of internal lysine residues of core histone N-terminal domains has been found correlatively associated with transcriptional activation in eukaryotes for more than three decades. Recent discoveries showing that several transcriptional regulators possess intrinsic histone acetyltransferase (HAT) and deacetylase (HDAC) activities strongly suggest that histone acetylation and deacetylation each plays a causative role in regulating transcription. Intriguingly, several HATs have been shown an ability to acetylate nonhistone protein substrates (e.g., transcription factors) in vitro as well, suggesting the possibility that internal lysine acetylation of multiple proteins exists as a rapid and reversible regulatory mechanism much like protein phosphorylation. This article reviews recent developments in histone acetylation and transcriptional regulation. We also discuss several important, yet unanswered, questions.